MENINGKATKAN KEMAMPUAN MENULIS KARANGAN DESKRIPSI MELALUI MEDIA AMPLOP MISTERI PADA MURID KELAS IV SEKOLAH DASAR - Reyhani, Delia Putri; Husain, Rusmin; Pulukadang, Wiwy Triyanty; Monoarfa, Fidyawati; Katili, Sukri (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
ABSTRACT Language learning in elementary schools is closely related to the development of writing skills, one of which is the ability to compose descriptive essays. Field observations indicate that there are still students who are not yet able to develop and express their ideas optimally in written form. A similar condition was also found among fourth-grade students at SDN 1 Batudaa, Gorontalo Regency, where the students’ ability to write descriptive essays has not yet developed optimally. Efforts to improve students’ ability to write descriptive essays therefore became the main focus of this study, which was carried out through the implementation of the Mystery Envelope learning media in the classroom. This study employed a Classroom Action Research (CAR) approach conducted through two cycles of action. Each cycle consisted of the stages of planning, action implementation, observation, and reflection, which aimed to improve the learning process. The research subjects consisted of 20 fourth-grade students. To obtain the research data, the researcher used several data collection techniques, namely observation, interviews, tests, and documentation. The students’ ability to write descriptive essays showed gradual improvement along with the implementation of actions in each research cycle. In Cycle I, the number of students who achieved mastery increased from 4 students (20%) at the first meeting to 10 students (50%) at the second meeting. In Cycle II, the number of students achieving mastery increased from 14 students (70%) at the first meeting to 17 students (85%) at the second meeting. The implementation of the Mystery Envelope media in learning demonstrated positive results, namely an improvement in the ability of fourth-grade students at SDN 1 Batudaa, Gorontalo Regency, to write descriptive essays. ABSTRAK Pembelajaran bahasa di sekolah dasar tidak terlepas dari pengembangan kemampuan menulis, salah satunya melalui keterampilan menyusun karangan deskriptif. Fakta di lapangan menunjukkan bahwa masih terdapat siswa yang belum mampu mengembangkan serta menyampaikan gagasan mereka secara optimal dalam bentuk tulisan. Pada siswa kelas IV SDN 1 Batudaa Kabupaten Gorontalo juga ditemukan kondisi yang serupa, yaitu kemampuan menulis karangan deskripsi yang masih belum berkembang secara optimal. Upaya peningkatan kemampuan siswa dalam menulis karangan deskripsi menjadi fokus utama dalam penelitian ini, yang dilaksanakan melalui penerapan media Amplop Misteri dalam pembelajaran. Pendekatan yang digunakan dalam penelitian ini adalah Penelitian Tindakan Kelas (PTK) yang dilaksanakan melalui dua siklus tindakan. Setiap siklus meliputi tahap perencanaan, pelaksanaan tindakan, observasi, dan refleksi yang bertujuan untuk memperbaiki proses pembelajaran. Subjek penelitian berjumlah 20 siswa kelas IV. Untuk memperoleh data penelitian, peneliti menggunakan beberapa teknik pengumpulan data, yaitu observasi, wawancara, tes, serta dokumentasi. Kemampuan siswa dalam menulis karangan deskripsi menunjukkan perkembangan yang semakin baik seiring dengan pelaksanaan tindakan pada setiap siklus penelitian. Pelaksanaan Siklus I menunjukkan adanya peningkatan jumlah siswa yang mencapai ketuntasan, dari 4 siswa (20%) pada pertemuan pertama menjadi 10 siswa (50%) pada pertemuan kedua. Pelaksanaan Siklus II memperlihatkan peningkatan jumlah siswa yang mencapai ketuntasan, yaitu dari 14 siswa (70%) pada pertemuan pertama menjadi 17 siswa (85%) pada pertemuan kedua. Penerapan media Amplop Misteri dalam pembelajaran menunjukkan hasil yang positif, yaitu meningkatnya kemampuan siswa kelas IV SDN 1 Batudaa Kabupaten Gorontalo dalam menulis karangan deskripsi.